The Development of House Contruction in Villa Wira Karya Complex - Noraidarayanti Noraidarayanti; Bambang Subiyakto; Fatwa Nur'aini; Sigit Triyono; Syarifuddin Syarifuddin (Universitas Lambung Mangkurat, 2024)
Among the various modern-style housing in Pasar Kamis Village, Kertak Hanyar Subdistrict, Banjar Regency, one can find houses that combine local wisdom backgrounds. Houses in Pasar Kamis Village incorporate local wisdom contexts with house building designs resembling Banjar palimasan houses, which were used during the kingdom era as treasurer's residences for caring for the kingdom's gold and silver. This study uses descriptive methodology based on qualitative approach to analyze the development of housing construction in Villa Wira Karya Complex and to characterize the process of house manifestation in Villa Wira Karya Complex by collecting data through the community of Villa Wira Karya Complex and housing real estate developers. Data collection techniques are conducted through residence observation, especially in Villa Wira Karya Complex in Pasar Kamis Village, interviews, and documentation and photography. The development of traditional houses to modern houses in Villa Wira Complex represents a significant shift towards modern design and technology, including aspects of design, more modern building materials, and benefits. The development in Villa Wira Karya Complex covers aspects of design, building materials of the houses, as well as the usefulness of the house ornaments, reflecting adaptation to the times. Houses in Villa Wira Karya Complex, adopting the concept of local wisdom such as Banjar Palimasan houses, are an important part of cultural heritage and local identity that must be preserved.